Integrated Molecular-To-Industrial Optimization: A Framework For Flow Assurance, Catalytic Processing, And Circular Sustainability In The Chemical Industry - Muhibullah Visal; Shirpacha Khapulwak (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The modern chemical and petrochemical industries face a complex triad of challenges encompassing flow assurance risks in extreme environments, optimization of catalytic processes for high-value chemical synthesis, and achievement of aggressive decarbonization targets mandated by global sustainability frameworks. Current literature predominantly addresses these domains in isolation, resulting in a fragmented understanding of the interdependencies between molecular-level phenomena, reactor-scale engineering, and systemic sustainability constraints. This systematic review synthesizes eighty peer-reviewed studies published between 2015 and 2026, utilizing PRISMA methodology and quality assessment protocols to bridge this multi-scale gap. The thematic synthesis reveals a critical efficiency-sustainability trade-off wherein traditional flow assurance solutions directly conflict with carbon reduction mandates, alongside a significant modeling gap whereby molecular-scale insights fail to translate into macroscopic kinetic models due to absent meso-scale translation methodologies. To resolve these structural contradictions, this review proposes the Integrated Molecular-to-Industrial Sustainability Loop (IMISL) framework, conceptualizing the industry as a closed-loop system where systemic sustainability constraints provide direct feedback to molecular design and process engineering layers. The IMISL framework enforces co-optimization of operational efficacy and environmental impact from the earliest stages of catalyst or inhibitor design, offering a novel pathway for transitioning the chemical industry from linear carbon-intensive operations to sustainable, digitally integrated manufacturing paradigms.